Trigonometric formulas doesn't work here

Geometry Level 3

Evaluate:

cos ( π 11 ) + cos ( 3 π 11 ) + cos ( 5 π 11 ) + cos ( 7 π 11 ) + cos ( 9 π 11 ) = ? \cos \left(\frac{\pi}{11}\right)+\cos \left(\frac{3\pi}{11}\right)+\cos\left(\frac{5\pi}{11}\right) + \cos\left(\frac{7\pi}{11}\right) +\cos\left(\frac{9\pi}{11}\right)=?

Problem is not original

1 2 \frac{1}{2} 3 4 \frac{3}{4} 1 4 \frac{1}{4} 1 6 \frac{1}{6} 1 π \frac{1}{\pi}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
May 8, 2019

For any positive integer n n , the roots of X n + 1 = 0 X^n + 1 = 0 are 1 -1 and e ± ( 2 k + 1 ) π i 2 n + 1 e^{\pm\frac{(2k+1)\pi i}{2n+1}} for 0 k n 1 0 \le k \le n-1 . Thus the sum of these roots is 0 0 , and hence 0 = 1 + k = 0 n 1 ( e ( 2 k + 1 ) π i 2 n + 1 + e ( 2 k + 1 ) π i 2 n + 1 ) = 1 + 2 k = 0 n 1 cos ( ( 2 k + 1 ) π 2 n + 1 ) 0 \; = \; -1 + \sum_{k=0}^{n-1} \left(e^{\frac{(2k+1)\pi i}{2n+1}} + e^{-\frac{(2k+1)\pi i}{2n+1}}\right) \; = \; -1 + 2\sum_{k=0}^{n-1} \cos\left(\frac{(2k+1)\pi}{2n+1}\right) so that k = 0 n 1 cos ( ( 2 k + 1 ) π 2 n + 1 ) = 1 2 \sum_{k=0}^{n-1} \cos\left(\frac{(2k+1)\pi}{2n+1}\right) \; = \; \boxed{\frac12}

In general, k = 0 n 1 cos ( 2 k + 1 2 n + 1 ) = 1 2 \displaystyle \sum_{k=0}^{n-1} \cos \left(\frac {2k+1}{2n+1} \right) = \dfrac 12 (see proof here ).

@Hana Wehbi Use \left( \right) for brackets. They will adjust their size accordingly.

Chew-Seong Cheong - 2 years, 1 month ago

Ok l will try, thanks.

Hana Wehbi - 2 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...